Integration of Freirean Thinking in University Work: Towards a Transformation of One's Own Praxis - Olivares Garita, Cinthya (2020)
Based on Pablo Freire’s thinking and other experts’ mentioned in this essay, the author analyzes critically university professors’ weaknesses and the educational system’s in general. Four transforming actions inspired by Freire’s ideas about dialogicity, pedagogy of the question, the reflection-action dialectical binomial, and critical literacy are explored. This essay aims to foster self-awareness in university professors for the purpose of freeing their praxis from traditional vices and boosting the transformation of the students as a result of that liberation.